2015
DOI: 10.1097/sla.0000000000000614
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Hepatic Artery Infusional and Systemic Chemotherapy for Patients With Unresectable Hepatic Metastases From Colorectal Cancer

Abstract: Purpose Evaluate conversion rate of patients with unresectable colorectal-liver metastasis to complete resection with hepatic-arterial infusion plus systemic chemotherapy including bevacizumab. Patients and Methods Forty-nine patients with unresectable CRLM were included in a single-institution phase II trial. Conversion to resection was the primary outcome. Secondary outcomes included overall (OS), progression-free survival (PFS), and response rates (RR). Multivariate and Landmark analyses were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
124
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(127 citation statements)
references
References 46 publications
1
124
0
2
Order By: Relevance
“…In one randomized study, a significant survival benefit is reported for patients undergoing continuous HAI with 5-fluoro-deoxy-uridine (FUDR) compared with the control arm (5-fluoro-uracil (5FU)/BMT) (13.5 versus 7.5 months; p=0.03)) [28]. Recent results of a non-controlled trial promote HAI in combination with systemic chemotherapy including bevacizumab [29]. The overall response rate was 76 % (inclusive of 4 complete responses), and 23 patients (47 %) achieved conversion to resection at a median of 6 months from initial treatment.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In one randomized study, a significant survival benefit is reported for patients undergoing continuous HAI with 5-fluoro-deoxy-uridine (FUDR) compared with the control arm (5-fluoro-uracil (5FU)/BMT) (13.5 versus 7.5 months; p=0.03)) [28]. Recent results of a non-controlled trial promote HAI in combination with systemic chemotherapy including bevacizumab [29]. The overall response rate was 76 % (inclusive of 4 complete responses), and 23 patients (47 %) achieved conversion to resection at a median of 6 months from initial treatment.…”
Section: Introductionmentioning
confidence: 95%
“…Patients who had undergone resection had a better overall survival than those who did not (3-year overall survival of 80 versus 26 %). Ten of 49 (20 %) of the patients with surgical resection had no evidence of disease at a median follow-up of 39 months (32-65 months) [29]. Procedure-related specific complications of HAI such as hepatic artery dissection and thrombosis, portcatheter occlusion as well as pump failure and infection are reported in up to 21, 5, 2, and 3 %, respectively [30].…”
Section: Introductionmentioning
confidence: 97%
“…3 Although the patient population and interventions are similar, the two studies have some notable differences. D'Angelica and colleagues at MSKCC performed a prospective, phase 2 clinical trial for HAI combined with systemic therapy, using conversion to resectability as the primary outcome.…”
Section: 3mentioning
confidence: 99%
“…In patients who were chemotherapynaïve, the median survival was 50.8 months, and for patients who were previously treated the median survival was 35 months. D'Angelica et al [53] evaluated 49 patients with unresectable liver metastases from CRC treated with HAI plus systemic chemotherapy in a prospective study. The overall response rate was 76%, 47% of patients were converted to resection at 6 months after treatment start, and median overall survival for all patients was 38 months.…”
Section: Role Of Hepatic Arterial Infusion In the Metastatic Setting:mentioning
confidence: 99%